A review on knowledge, perception, practice and associated factors of sunscreen Usage among the population - Abd Hisham, Nursyafiah Yasmin; Mahat, Nur Ain; Ramli, Muhammad Afiq Ikhmal; Shaharaan, Noor Maizatul Akma (IIUM Press, 2024)
Background: The use of sunscreen is a critical component of skin cancer prevention and overall skin health. Nevertheless, inconsistencies in sunscreen knowledge, perceptions, and practices persist among different populations, which are influenced by various factors. This review aims to synthesise and analyse the existing literature on the knowledge, perceptions, and practices related to sunscreen use across different populations and regions. It explores the factors influencing sunscreen application and the barriers to proper sunscreen use. Methods: A comprehensive review of studies published between 2015 and 2023 was conducted, focusing on quantitative research on sunscreen knowledge, perceptions, and practices. Journals were obtained from EBSCo, Scopus and Mendeley databases. Results: The initial article obtained from databases was 1250 articles, and the final articles chosen for review is 32 articles. This review highlights significant knowledge gaps about sunscreen use, particularly the need for sunscreen on cloudy days and understanding SPF values. Despite high awareness of UV radiation's harmful effects, actual use remains inconsistent. Common misconceptions, such as believing sunscreen is unnecessary in winter or indoors, persist across demographics. Perceptions of sunscreen's efficacy vary. Factors like sex, skin phototype, age, and education level significantly influence use, with barriers including forgetfulness, discomfort, cost, and lack of habit. Conclusion: The findings underscore the need for enhanced educational campaigns to correct misconceptions and promote consistent sunscreen use. Targeted interventions should address specific barriers and tailor messages to different demographic groups to improve sunscreen practices and reduce the risk of UV-induced skin damage.